Association between ACTN3 R577X genotype and risk of non-contact injury in trained athletes: A systematic review - Zouhal, H.; Del Coso, J.; Jayavel, A.; Tourny, C.; Ravé, G.; Jebabli, N.; Clark, C. C. T.; Barthélémy, B.; Hackney, A. C.; Abderrahman, A. B. (Journal of Sport and Health Science, 2023)
Purpose The aim of this study was to review, systematically, evidence concerning the link between the ACTN3 R577X polymorphism and the rates and severity of non-contact injuries and exercise-induced muscle damage in athletes and individuals enrolled in exercise training programs.